2023
DOI: 10.3389/fphar.2023.1176206
|View full text |Cite
|
Sign up to set email alerts
|

Impact of glucagon-like peptide 1 receptor agonist liraglutide and dipeptidyl peptidase-4 inhibitor sitagliptin on bowel cleaning and gastrointestinal symptoms in type 2 diabetes

Abstract: Objective: Glucagon-like peptide 1 receptor agonists (GLP-1 RAs) and dipeptidyl peptidase-4 inhibitors (DPP-4i) profoundly affect the gastrointestinal motor system, which may increase the incidence of inadequate bowel cleaning and gastrointestinal symptoms. Hence, this observational study mainly aimed to assess the influence of GLP-1 RAs liraglutide and DPP-4i sitagliptin on bowel preparation in type 2 diabetes (T2DM).Method: This observational study consecutively enrolled T2DM scheduled for a colonoscopy. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…According to a retrospective study conducted by Yao et al [ 26 ], 15.5% of patients receiving GLP-1 RA had a Boston Bowel Preparation Scale (BBPS) score of less than 5, compared to 6.6% of patients not receiving GLP-1 RA[ 26 ]. An observational study done by Tong et al [ 27 ] did not notice a significant difference in the incidence of inadequate bowel preparation on colonoscopy in patients taking Liraglutide, Sitagliptin, and patients not on GLP-1 RA. In the subgroup analyses it was shown that type 2 diabetes patients with diabetic neuropathy on Liraglutide were more likely to have inadequate bowel prep (61.3%) as compared to patients in Sitagliptin group (32.1%; P = 0.022) and control group (32.8% P = 0.025)[ 27 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to a retrospective study conducted by Yao et al [ 26 ], 15.5% of patients receiving GLP-1 RA had a Boston Bowel Preparation Scale (BBPS) score of less than 5, compared to 6.6% of patients not receiving GLP-1 RA[ 26 ]. An observational study done by Tong et al [ 27 ] did not notice a significant difference in the incidence of inadequate bowel preparation on colonoscopy in patients taking Liraglutide, Sitagliptin, and patients not on GLP-1 RA. In the subgroup analyses it was shown that type 2 diabetes patients with diabetic neuropathy on Liraglutide were more likely to have inadequate bowel prep (61.3%) as compared to patients in Sitagliptin group (32.1%; P = 0.022) and control group (32.8% P = 0.025)[ 27 ].…”
Section: Discussionmentioning
confidence: 98%
“…An observational study done by Tong et al [ 27 ] did not notice a significant difference in the incidence of inadequate bowel preparation on colonoscopy in patients taking Liraglutide, Sitagliptin, and patients not on GLP-1 RA. In the subgroup analyses it was shown that type 2 diabetes patients with diabetic neuropathy on Liraglutide were more likely to have inadequate bowel prep (61.3%) as compared to patients in Sitagliptin group (32.1%; P = 0.022) and control group (32.8% P = 0.025)[ 27 ]. A retrospective medical record analysis done by Sharma et al [ 28 ], on type 2 diabetes patients in GLP-1 RA showed no significant difference between the groups.…”
Section: Discussionmentioning
confidence: 98%
“…There is limited data on the impact of GLP-1RA on bowel preparation. Tong et al (7) published a recent null study finding that the GLP1-RA liraglutide did not markedly influence the incidence of inadequate bowel cleaning; however, liraglutide was found to increase the incidence of inadequate bowel preparation in patients with type 2 diabetes with diabetic peripheral neuropathy, suggesting a need for more focused and aggressive bowel preparation regimens for this specific group. Sharma et al (8) previously investigated this in a retrospective study among a diabetic population, finding no significant differences in bowel preparation among patients taking GLP-1RA and those not.…”
Section: Discussionmentioning
confidence: 99%